Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4102/phcfm.v7i1.875
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in rural communities in Delta State, Nigeria: Prevalence, risk factors and barriers to health care

Abstract: IntroductionHypertension is a global health challenge and its prevalence is increasing rapidly amongst adults in many African countries. Some studies on the prevalence and risk factors of hypertension have been conducted in Nigeria, but none within Delta State. We assessed the prevalence of hypertension and associated risk factors amongst adults in three villages in the Ibusa community in Delta State, Nigeria.MethodHomesteads were randomly selected and all consenting adults (≥ 18 years of age) were recruited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 15 publications
(22 reference statements)
3
19
3
Order By: Relevance
“…Onwuchekwa et al, reported a prevalence of 18.3% in Kegbara-Dere in Rivers State, Ofili et al, 44% in Delta State, Isara et al (37.8%) in Edo state and Akpan et al, (44.3%) in Akwa-Ibom. [22][23][24][25] This wide margin may suggest an upsurge in prevalence of hypertension in recent years. It also suggests that rural communities are not left out in this rampaging scourge.…”
Section: Discussionmentioning
confidence: 99%
“…Onwuchekwa et al, reported a prevalence of 18.3% in Kegbara-Dere in Rivers State, Ofili et al, 44% in Delta State, Isara et al (37.8%) in Edo state and Akpan et al, (44.3%) in Akwa-Ibom. [22][23][24][25] This wide margin may suggest an upsurge in prevalence of hypertension in recent years. It also suggests that rural communities are not left out in this rampaging scourge.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors affecting adherence include unrealistic expectations of treatment such as a cure for their hypertension, depression from being newly diagnosed or knowing that hypertension is not curable, as well as the use of herbal preparations [9,10,12,31]. Unavailability of antihypertensive medicines at PHC facilities, a low level of formal education, and other factors such as the distance to treatment facilities, medication costs, and the availability of professional guidance, are also associated with nonadherence to treatment [7,9,12,16,30,32].…”
Section: Introductionmentioning
confidence: 99%
“…It is also higher than the rates observed in Cameroon and India (Midha et al, 2009;Pancha Mbouemboue et al, 2016). This prevalence is comparable to that observed by Ofili and Adeloye in Nigeria (Adeloye and Basquill, 2014;Ofili et al, 2015).…”
Section: Prevalence Of Hypertensionmentioning
confidence: 51%
“…In Ethiopia, Kenya, and Uganda, other studies have found hypertension's prevalence of 27.9, 22.8 and 15%, respectively (Joshi et al, 2014;Abebe et al, 2015;Kayima et al, 2015). Factors independently and commonly associated with hypertension are advanced age and overweight or near-constant obesity, high salt intake (Ofili et al, 2015), urban area of residence, sex, age and education level (Okpechi et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation